Quasi-static axial crushing of segmented and non-segmented composite tubes - Abosbaia, A.A.S; Mahdi, E; Hamouda, A.M.S; Sahari, B.B (Elsevier, 2003)
This paper examines the effect of segmentation on the crushing behaviour, energy absorption and failure mechanism of composite tubes. Quasi-static axial crushing behaviour of segmented and non-segmented composite tubes is investigated experimentally. The segmented composite tube consists of three different material regions, each with its own specific functions. Load-displacement curves and deformation histories of typical specimens are presented and discussed. The results showed that non-segmented composite tubes were found to be very brittle (i.e. the tissue mat glass fibre/epoxy tubes), or have low energy absorption capability (i.e. cotton fabric fibre/epoxy). On the other hand, segmented composite tubes including the tissue mat glass fibres were found to suffer from low energy absorption and the catastrophic failure mechanism initiated at the part made of tissue mat glass fibre/epoxy. Segmented composite tubes from carbon fabric fibre and cotton fabric fibres exhibited good energy absorption capability as well as stable load-carrying capacity.